Quid tibi surrupui? The lexical and semantic configuration of furtum in Aulularia (Circe de clásicos y modernos, 2018)
Roman law included furtum within the sphere of private crimes. This delictum, mentioned in the Twelve Tables Law, has a relevant importance in Plautus’ comedies and in the development of the plot. This article will study the furtum in Aulularia on the basis of the analysis of it’s lexical and semantic configuration. We will outline the scope of the various verbs related to such a crime, allowing us to see, in the social order, the balance of power (uis et uiolentia) prevailing when the boundaries of the community and citizenship are violated.
Keywords: Plautus; fortum; semantic; transgression